UK doctors' views on the implementation of the European Working Time Directive as applied to medical practice: a qualitative analysis. Issue 2 (6th February 2014) - Clarke, Rachel T; Pitcher, Alex; Lambert, Trevor W; Goldacre, Michael J
Abstract : Objectives: To report on what doctors at very different levels of seniority wrote, in their own words, about their concerns about the European Working Time Directive (EWTD) and its implementation in the National Health Service (NHS). Design: All medical school graduates from 1993, 2005 and 2009 were surveyed by post and email in 2010. Setting: The UK. Methods: Using qualitative methods, we analysed free-text responses made in 2010, towards the end of the first year of full EWTD implementation, of three cohorts of the UK medical graduates (graduates of 1993, 2005 and 2009), surveyed as part of the UK Medical Careers Research Group's schedule of multipurpose longitudinal surveys of doctors. Results: Of 2459 respondents who gave free-text comments, 279 (11%) made unprompted reference to the EWTD; 270 of the 279 comments were broadly critical. Key themes to emerge included frequent dissociation between rotas and actual hours worked, adverse effects on training opportunities and quality, concerns about patient safety, lowering of morale and job satisfaction, and attempts reportedly made in some hospitals to persuade junior doctors to collude in the inaccurate reporting of compliance. Conclusions: Further work is needed to determine whether problems perceived with the EWTD, when they occur, are attributable to the EWTD itself, and shortened working hours, or to the way that it has been implemented in some hospitals.